Pengaruh Citra Merek dan Promosi terhadap Keputusan Pembelian Mobil Suzuki APV (Studi pada PT. Arindo Gedong Jembar Tegal) - Ferry Yahya; Apriatni Endang Prihatini; Reni Shinta Dewi (Universitas Diponegoro, 2015)
This research is motivated by competition brand in Low car segment MPV. Suzuki brand car sales in 2013 based Gaikindo be in the top four nationally and has yet to reach a specified target. In particular, this study discusses the Low MPV Suzuki APV cars at PT . Arindo gedong Jembar Tegal that sales decreased in the last two years. The purpose of research to determine the influence of brand image and promotion on purchase decisions Suzuki APV (Studies in PT. Arindo Gedong Jembar Tegal). This research method is explanatory, data collection techniques by questionnaires, observation, and literature study. Purposive sampling technique is used with a sample of 78 people. The analysis technique used was qualitative and quantitative using validity, reliability test, correlation coefficient, simple and multiple regression analysis, the coefficient of determination, cross tabulation, and the significance test ( t test and F test ). Results and discussion showed a positive influence on the brand image on purchasing decisions. Promotion positive influence on purchase decisions. Brand image and promotion jointly positive influence on purchasing decisions. Suggestions in this study ,PT. Arindo Gedong Jembar should enhance the brand image of Suzuki APVby improve after-sales service, increase understanding of the explanation of product knowledge Suzuki APV, and also increases the intensity of the promotion through social media, outdoor media, sponsorship and giving special training about technique of delivering information for salesman and verbally skills in conveying information in order to increase the purchase of Suzuki APV cars.